The Effectiveness of Intraocular Methotrexate in the Treatment of Posterior Uveitis in Behçet’s Disease Patients Compared to Retrobulbar Steroids Injection - Hossam El Din Mohamed Khalil; Heba A. El Gendy; Hala Ahmed Raafat Youssef; Hazem Effat Haroun; Tamer Atef Gheita; Hossam Mahmoud Bakir (Journal of Ophthalmology)
Aim of Work. To evaluate the efficacy of intravitreal methotrexate (MTX) compared to retrobulbar triamcinolone acetonide (TAA), in controlling posterior segment involvement and inducing remissions among Behçet’s disease (BD) patients. Study Design. This is a cross-sectional nonrandomized comparative study. Patients and Methods. 31 adult BD male patients with a mean disease duration of 5.45 years who presented with bilateral posterior segment involvement were included. Each patient received intravitreal injection of 400 μg/0.1 mL (MTX) for the right eye (Group A) and 1 mL of retrobulbar 40 mg/mL TAA for the left eye (Group B). Results. 90% of eyes showed complete improvement of anterior chamber reaction, whereas an improvement in vitreous activity in 77% with no significant differences between both groups (p≤0.1). BCVA improved in 77.4% eyes (Group A) compared to 87.1% (Group B) (p≤0.4). Relapses were noted in 11 eyes (35.5%), in group A, with the mean duration of remission being 19.1 weeks ± 2.13 compared to 7.35±2.8 in 20 eyes (64.5%) in group B (p≤0.1). Conclusion. No statistical differences were found between both treatment modalities; however, based on clinical observations, intravitreal MTX may ensure better control of inflammatory reaction and may encourage longer remission as compared to retrobulbar TAA in BD patients.